A cost analysis comparing telepsychiatry to in-person psychiatric outreach and patient travel reimbursement in Northern Ontario communities. (December 2020) - Serhal, Eva; Lazor, Tanya; Kurdyak, Paul; Crawford, Allison; de Oliveira, Claire; Hancock-Howard, Rebecca; Coyte, Peter C
Introduction: Residents of Northern Ontario have limited access to local psychiatric care. To address this, three program models exist: (1) telepsychiatry; (2) psychiatrists traveling to underserved areas; and (3) reimbursing patients for travel to a psychiatrist. Evidence shows that telepsychiatry has comparable outcomes to in-person consultations. The objective of this study was to determine the cost difference between programs. Methods: A cost-minimization analysis estimating cost per visit from a public healthcare payer economic costing perspective was conducted. Data on fixed and variable costs were obtained. Evidence-based assumptions were made where relevant. Base-case scenarios and a break-even analysis were completed, as well as deterministic and probabilistic sensitivity analyses, to explore the effects of parameter variability on program costs. Results: Costs per visit were lowest in telepsychiatry (CAD360) followed by traveling physicians (CAD558) and patient reimbursement (CAD620). Among the 100, 000 Monte Carlo simulations, results showed telepsychiatry was the least costly program in 71.2% of the simulations, while the reimbursement and outreach programs were least costly in 15.1% and 13.7% of simulations, respectively. The break-even analysis found telepsychiatry was the least costly program after an annual patient visit threshold of approximately 76 visits (compared to traveling psychiatrists) and 126 visits (compared to reimbursed patients). Discussion: Our analyses support telepsychiatry as the least costly program. These results have important implications for program planning, including the prioritization of telepsychiatry, increased integration of telepsychiatry with other modalities of outreach psychiatry, and limiting use of the patient remuneration program to where medically necessary, to reduce overall cost.